Effects of warming on the degradation and production of low-molecular-weight labile organic carbon in an Arctic tundra soil. (April 2016) - Yang, Ziming; Wullschleger, Stan D.; Liang, Liyuan; Graham, David E.; Gu, Baohua
Abstract: The fate of soil organic carbon (SOC) stored in the Arctic permafrost is a key concern as temperatures continue to rise in the northern hemisphere. Studies and conceptual models suggest that degradation of SOC is affected by its composition, but it is unclear exactly which SOC fractions are vulnerable to rapid breakdown and what mechanisms may be controlling SOC degradation upon permafrost thaw. Here, we examine the dynamic consumption and production of labile SOC in an anoxic incubation experiment using soil samples from the active layer at the Barrow Environmental Observatory, Barrow, Alaska, USA. Free-reducing sugars, alcohols, and low-molecular-weight (LMW) organic acids were analyzed during incubation at either −2 or 8 °C for up to 240 days. Results show that degradation of simple sugar and alcohol in SOC largely accounts for the initial rapid release of CO2 and CH4 through anaerobic fermentation, whereas the fermentation products, acetate and formate, are subsequently utilized as primary substrates for methanogenesis. Iron(III) reduction is correlated with acetate production and methanogenesis, suggesting its important role as an electron acceptor in SOC respiration in tundra environment. These observations are further supported in a glucose addition experiment, in which rapid CO2 and CH4 production occurred concurrently with rapid production and consumption of labile organics such as acetate. However, addition of tannic acid, as a more complex organic substrate, showed little influence on the overall production of CO2 and CH4 and organic acids. Together our study shows that LMW labile SOC controls the initial rapid release of green-house gases upon warming of permafrost soils. We present a conceptual framework for the labile SOC transformations and their relations to fermentation, iron reduction and methanogenesis, thereby providing the basis for improved model prediction of climate feedbacks in the Arctic. Graphical abstract: Highlights: We identify labile soil organic carbon (SOC) degradation and production during permafrost thaw. Labile SOC is largely responsible for initial rapid CO2 and CH4 emission upon warming. Consumption of acetate strongly correlates with methanogenesis and Fe(III) reduction. We propose a conceptual framework of labile SOC degradation and production in Arctic soils.